Hedgehog−Gli2 Signaling Promotes Chemoresistance in Ovarian Cancer Cells by Regulating MDR1 - Wang, Qian; Wei, Xin; Hu, Lanyan; Zhuang, Lingling; Zhang, Hong; Chen, Qi (Frontiers in Oncology, 2022)
Background: Cisplatin (DDP) resistance remains a key challenge in improving the clinical outcome of patients with ovarian cancer (OC). Gli2 overexpression can lead to DDP resistance in OC cells, but the specific underlying regulatory mechanism remains unclear. The membrane transporter encoding gene MDR1 positively regulates chemotherapy resistance in various cancer types. We evaluated MDR1 as a potential Gli2 downstream target and the contribution of the Gli2/MDR1 axis in promoting DDP resistance in OC cells. Methods: To generate drug-resistant SKOV3/DDP cells, SKOV3 cells were grown for six months under continuous induction wherein the DDP concentration was steadily increased. Gli2 expression in OC cells with varying DDP sensitivities was detected using western blot. Cell counting kit-8 assays were used to assess the DDP sensitivity of SKOV3, SKOV3/DDP, A2780, and A2780/DDP cells and reversal of DDP resistance in SKOV3/DDP and A2780/DDP cells. Cell proliferation was analyzed using 5-ethynyl-2′-deoxyuridine (EdU) incorporation assays. The transcriptional regulation of MDR1 by Gli2 was determined using luciferase reporter assays. Xenograft OC tumors were generated in nude mice, which were then treated with intraperitoneal DDP or phosphate-buffered saline injections to investigate if Gli2 affected DDP resistance in OC in vivo. Results: DDP-resistant SKOV3/DDP and A2780/DDP cells showed higher expression of Gli2 and MDR1 as compared with that in DDP-sensitive OC cells. Gli2 knockdown in SKOV3/DDP cells significantly reduced MDR1 expression, whereas it increased DNA damage, thereby sensitizing OC cells to DDP. Similar results were obtained after targeting Gli2 expression with the Gli-antagonist 61 inhibitor in SKOV3/DDP and A2780/DDP cells. In cells stably overexpressing Gli2, treatment with gradient concentrations of verapamil, an MDR1 inhibitor, significantly inhibited MDR1 expression. Our findings indicate that downregulation of MDR1 expression may reverse OC cell resistance to DDP. Dual-luciferase reporter gene assays confirmed that MDR1 is a direct downstream target of Gli2, with Gli2 positively regulating MDR1 expression. Subcutaneous xenotransplantation in nude mice demonstrated that Gli2 plays a key role in regulating OC drug resistance. Conclusions: We identified a mechanism by which Hedgehog-Gli signaling regulates OC chemoresistance by modulating MDR1 expression. Gli2 and MDR1 are potential biomarkers and therapeutic targets in patients with chemoresistant OC.